Novelties of the Russian Electoral Legal System in the Context of International Electoral Standards - A. V. Zhilyaev (Сибирское юридическое обозрение, 2012)
The article deals with the problems of international selective standards realization in the Russian electoral legal system. The author analyzes the changes and additions brought into domestic laws on elections during the last four years. The degree of their compliance to provisions of the international legal acts containing the international selective standards is defined. The ways of existing problems solution concerning legal regulation of the public relations sphere are considered.